Rekayasa Nanoselulosa Bakteri sebagai Platform Nano-Biomaterial untuk Terapi Obat dan Antimikroba: Perspektif Pengobatan Modern - Zakia Asrifah Ramly (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Antimicrobial resistance (AMR) continues to rise globally, diminishing the efficacy of conventional antibiotics and driving the need for advanced biomaterial-based therapeutic strategies. Bacterial nanocellulose (BNC) has emerged as a highly promising platform due to its nanoscale fibrillar structure, high porosity, exceptional purity, and excellent biocompatibility. Its large surface area and hydrogel-like properties enable high drug-loading capacity and controlled release, making BNC an ideal matrix for therapeutic delivery. Functionalization of BNC with metallic nanoparticles (AgNP, ZnO, CuO), antibiotics, plant-derived bioactives (e.g., quercetin, curcumin), and innovative agents such as lytic enzymes or metal–organic frameworks has demonstrated markedly enhanced antibacterial and antibiofilm performance. In vitro studies report broad- spectrum inhibition, biofilm reduction up to 95%, and improved drug stability through sustained release. In vivo evaluations using wound models reveal accelerated healing (30–50%), reduced bacterial burden by up to 4 log CFU, and superior tissue regeneration with minimal systemic toxicity. Despite these promising outcomes, gaps remain regarding long-term safety, nanoparticle–host interactions, and standardized testing protocols. Overall, current evidence highlights BNC as a versatile and potent nanobiomaterial for antimicrobial therapy and drug delivery, although successful clinical translation will require comprehensive in vivo validation and methodological harmonization.